Comparison of airway immunopathology of eosinophilic bronchitis and asthma. Issue 6 (1st June 2003) - Brightling, C E; Symon, F A; Birring, S S; Bradding, P; Wardlaw, A J; Pavord, I D
Abstract : Background: Eosinophilic bronchitis is a condition characterised by a corticosteroid responsive cough, sputum eosinophilia, and normal tests of variable airflow obstruction and airway responsiveness. We performed a detailed comparative immunopathological study to test the hypothesis that the different airway function in patients with eosinophilic bronchitis and asthma reflects differences in the nature of the lower airway inflammatory response. Methods: Exhaled nitric oxide was measured and induced sputum, bronchoscopy, bronchial wash (BW), bronchoalveolar lavage (BAL), and bronchial biopsy were performed in 16 subjects with eosinophilic bronchitis, 15 with asthma, and 14 normal controls. Results: Both eosinophilic bronchitis and asthma were characterised by an induced sputum, BW and BAL eosinophilia, an increased number of epithelial and subepithelial eosinophils, and increased reticular basement membrane thickness. The median concentration of exhaled nitric oxide was higher in those with eosinophilic bronchitis (12 ppb) or asthma (8.5 ppb) than normal controls (2 ppb) (95% CI of the difference 5 to 16, p<0.0001 and 2 to 11.3, p=0.004, respectively). There were no group differences in epithelial integrity or the number of subepithelial T lymphocytes, mast cells or macrophages. Conclusion: With the exception of our previously reported association of smooth muscle mast cell infiltration with asthma, the immunopathology of eosinophilic bronchitis and asthma are similar which suggests that eosinophilic airway inflammation, increased exhaled nitric oxide, and increased basement membrane thickening are regulated independently of airway hyperresponsiveness.